Holons: towards a systematic approach to composing systems of systems - Blair, Gordon; Bromberg, Yérom-David; Coulson, Geoff; Elkhatib, Yehia; Réveillère, Laurent; Borba Ribeiro, Heverson; Rivière, Etienne; Taïani, François (: ACM, 2015)
The world’s computing infrastructure is increasingly differ- entiating into self-contained distributed systems with vari- ous purposes and capabilities (e.g. IoT installations, clouds, VANETs, WSNs, CDNs, . . . ). Furthermore, such systems are increasingly being composed to generate systems of sys- tems that offer value-added functionality. Today, however, system of systems composition is typically ad-hoc and fragile. It requires developers to possess an intimate knowledge of system internals and low-level interactions between their components. In this paper, we outline a vision and set up a research agenda towards the generalised programmatic construction of distributed systems as compositions of other distributed systems. Our vision, in which we refer uniformly to systems and to compositions of systems as holons, employs code generation techniques and uses common abstractions, operations and mechanisms at all system levels to support uniform system of systems composition. We believe our holon approach could facilitate a step change in the convenience and correctness with which systems of systems can be built, and open unprecedented opportunities for the emergence of new and previously-unenvisaged distributed system deploy- ments, analogous perhaps to the impact the mashup culture has had on the way we now build web applications.
, 2015
Keywords: System composition; Systems of systems; Distributed systems